"Smart" molecularly imprinted monoliths for the selective capture and easy release of proteins. Issue 16 (1st August 2016) - Wen, Liyin; Tan, Xinyi; Sun, Qi; Svec, Frantisek; Lv, Yongqin
Abstract : A new thermally switchable molecularly imprinted monolith for the selective capture and release of proteins has been designed. First, a generic poly(glycidyl methacrylate‐co‐ethylene dimethacrylate) monolith reacted with ethylenediamine followed by functionalization with 2‐bromoisobutyryl bromide to introduce the initiator for atom transfer radical polymerization. Subsequently, a protein‐imprinted poly( N ‐isopropylacrylamide) layer was grafted onto the surface of the monolithic matrix by atom transfer radical polymerization. Scanning electron microscopy and energy‐dispersive X‐ray spectroscopy of the cross‐sections of imprinted monoliths confirmed the formation of dense poly( N ‐isopropylacrylamide) brushes on the pore surface. The imprinted monolith exhibited high specificity and selectivity toward its template protein myoglobin over competing proteins and a remarkably large maximum adsorption capacity of 1641 mg/g. Moreover, this "smart" imprinted monolith featured thermally responsive characteristics that enabled selective capture and easy release of proteins triggered only by change in temperature with water as the mobile phase and avoided use of stronger organic solvents or change in ionic strength and pH.